2011
DOI: 10.1007/s11102-011-0326-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in acromegaly: description and brain volumetric correlates

Abstract: In acromegaly, we reported on increased rates of affective disorders such as dysthymia and depression, as well as structural brain changes. Objective of this study was to determine if cognitive impairments in patients with acromegaly exist and whether such impairments are associated with structural brain alterations defined by magnetic resonance imaging (MRI). In this cross-sectional study, 55 patients with biochemically confirmed acromegaly were enrolled. MRI data were compared with 87 control subjects. Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…However, recently a small study with 12 members of the Ecuadorian cohort of LS patients reported that they performed significantly better in memory tasks and had significantly lower cognitive impairment compared to their unaffected relatives (273). In human acromegaly patients, recent studies have reported cognition deficits, decreased short-term and long-term memory, anxiety and impaired decision making, and decreased activities in pre-frontal and mid-temporal cortices in brain (274,275,276,277). Interestingly, recent reports and multiple meta-analyses directly implicate a higher than normal serum IGF-1 as a disease trait marker in major depressive disorder (MDD) and bipolar disorder (BD) further stimulating the pleiotropy of GH action in cognitive development and maintenance (278,279,280,281).…”
Section: Cognitive Studies In Humans With Ghr Deficiencymentioning
confidence: 99%
“…However, recently a small study with 12 members of the Ecuadorian cohort of LS patients reported that they performed significantly better in memory tasks and had significantly lower cognitive impairment compared to their unaffected relatives (273). In human acromegaly patients, recent studies have reported cognition deficits, decreased short-term and long-term memory, anxiety and impaired decision making, and decreased activities in pre-frontal and mid-temporal cortices in brain (274,275,276,277). Interestingly, recent reports and multiple meta-analyses directly implicate a higher than normal serum IGF-1 as a disease trait marker in major depressive disorder (MDD) and bipolar disorder (BD) further stimulating the pleiotropy of GH action in cognitive development and maintenance (278,279,280,281).…”
Section: Cognitive Studies In Humans With Ghr Deficiencymentioning
confidence: 99%
“…6 They hypothesized that morphological changes in the brain occur during the first 10 years of hormone excess, and all of these effects on the brain are the result of the longlasting exposure of neuronal or glial cells to systemically elevated hormone levels. 6,15,30 In another study using MRI, Sievers et al 5 found a decrease in the hippocampal volume in patients with acromegaly. They concluded that in addition to the neuropsychological tests, MRI could be used in the diagnosis of cognitive impairment.…”
Section: 27mentioning
confidence: 97%
“…They concluded that in addition to the neuropsychological tests, MRI could be used in the diagnosis of cognitive impairment. 5 In the literature, the most important factors reported in the development of brain alterations are the elapsed time of diagnosis and control of disease. In this study, brain alterations were measured and followed by neurocognitive and psychiatric tests.…”
Section: 27mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the effect of the disease on the cognitive function of patients has been pointed out in the literature [23][24][25]. A study using event related potentials (ERPs) conducted by Tanriverdi et al provides electrophysiological evidence for cognitive dysfunction among people with excessive growth hormone secretion [23].…”
Section: The Psychological Social and Cognitive Functioning Of Patiementioning
confidence: 99%